2005
DOI: 10.1016/j.infsof.2004.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Parallel testing of distributed software

Abstract: The paper presents the experience of the use of parallel computing technologies to accelerate the testing of a complex distributed programming system such as Orbix 3, which is IONA's implementation of the CORBA 2.1 standard. The design and implementation of the parallel testing system are described in detail. Experimental results proving the high efficiency of the system are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…However, analyses under such circumstances can be impractical due to numbers of test cases or the fault space, particularly in the case of simultaneous fault models that demand consideration of fault combinations. Research has addressed these problems through leveraging parallel architectures in the execution of the large number of fault injection experiments [12], [13], though more scalable techniques have focused on sampling strategies for the test cases and error spaces [14], [15], [16].…”
Section: Related Workmentioning
confidence: 99%
“…However, analyses under such circumstances can be impractical due to numbers of test cases or the fault space, particularly in the case of simultaneous fault models that demand consideration of fault combinations. Research has addressed these problems through leveraging parallel architectures in the execution of the large number of fault injection experiments [12], [13], though more scalable techniques have focused on sampling strategies for the test cases and error spaces [14], [15], [16].…”
Section: Related Workmentioning
confidence: 99%
“…Alexey lastovetsky [2] focused on using parallel computing technologies to accelerate the testing of a complex distributed software system.Cyril Briquet [3] supported on evaluating the performance of scheduling algorithms. Performance is evaluated experimentally or through simulation.…”
Section: Related Workmentioning
confidence: 99%
“…In the case study presented by Lastovetsky and Alexey [25] it was shown that parallelizing regression testing for a distributed programming system resulted in a speed up of up to 7.7 on two 4-processor workstations.…”
Section: Parallel Execution Of Testingmentioning
confidence: 99%